Cesarean Section Rate in Tertiary Care Hospital of South Punjab using Robson Ten Group Classification System - Najam, Mehwish; Rasheed, Nuzhat (Journal of Fatima Jinnah Medical University, 2024)
Background: The rise in cesarean section rates throughout the world is a major public health issue and a topic of controversy because to the potential maternal and perinatal dangers, financial challenges, and discrepancy in access. This research set out to determine the high prevalence of cesarean sections using the Robson Ten Group Classification System (TGCS). Patients and Methods: The research was a cross-sectional prospective study. The TGCS was used to categorize all women who gave birth through lower segment cesarean section at Sheikh Zayed Hospital Rahim Yar Khan between January 2021 and July 2022. Rates of cesarean sections were determined both overall and by Robson group, as was each group's relative contribution to the cesarean section rate. Results: There were 543 (18.4%) females of age <20 years, 1826 (61.8%) females had age 20-30 years and 581 (19.6%) were aged 30-37 years. Out of 2950 females, 39.6% females fall in RTGCS class 5, followed by 2b (11.2%), 2a (10.4%), class 1 (9.7%), class 9 (7.8%) and class 10 (7.1%) and so on. Conclusion: Thus, RTGCS allows easy identiﬁcation of leading contributing patients groups. RTGCS can be effective criteria that can help to early predict the mode of delivery and prevent complications of cesarean section in several number of cases.